Interaction of Life Cycle Assessment (LCA) and BIM in a Construction Project to Reduce the Environmental Footprint - Osorio-Gómez, Cristian C.; Alzate-Buitrago, Alejandro; Amariles-López, Cristhian C.; Aristizábal-Torres, Daniel; Mancilla-Rico, Edwin A. (Civil Engineering Journal, 2025)
The construction sector is experiencing rapid growth in response to the increasing demand for new projects that address societal needs, making it one of the most significant contributors to greenhouse gas emissions. Therefore, it is essential to develop more sustainable and efficient construction processes that reduce the environmental impact in the sector. This study focuses on assessing the environmental footprint of a residential project in Colombia, based on the implementation of Building Information Modeling (BIM) with a sustainability focus. A Life Cycle Assessment (LCA) was performed using the "One Click LCA" software, where the characteristics of the building over a 50-year period were inserted and evaluated. The study determined the building’s environmental impacts and direct pollutant emissions, including global warming (CO2e), acidification (SO2e), eutrophication (PO4e), and ozone depletion (CFC), among others. The results were analyzed by evaluating their magnitude and criticality. One of the main findings was the emission of 1.49E+06 kg of CO2, which directly impacts global warming significantly. This LCA-BIM approach provides a transparent methodology for construction companies in Latin America to implement projects with a lower environmental impact, promoting sustainable practices within the industry. Doi: 10.28991/CEJ-2025-011-01-08 Full Text: PDF